Detailed shallow structure of the seismogenic fault of the 1976 Ms7.8 Tangshan earthquake, China - Liu, Kang; Li, Yigang; Nan, Yanyun; Liu, Baojin; Wang, Wanhe (Frontiers in Earth Science, 2022)
In 1976, a Ms7.8 strong earthquake occurred in the Tangshan region of northeast China within an ancient craton. In this study, we conducted shallow seismic exploration, drilling-based exploration, and exploratory trench excavation of ground fissures in the Tangshan fault zone, and obtained a high-resolution shallow seismic profile. Through analysis of its lithology and sedimentary cycle, we constructed a composite drilling profile across the faults. Coupled with the shallow fault combination patterns identified from the exploratory trenches, the profile reveals that the Guye-Nanhu fault was the shallow response fault in the seismogenic structure of the Tangshan earthquake. This fault is a strike-slip fault with a positive flower structure; the reverse fault branches become progressively steeper with depth and converge downward toward the vertical main strike-slip fault. A high-angle thrust fault is located to the west of the main strike-slip fault, and a series of small-scale normal faults appear in front of this fault owing to local extension. The tectonic form revealed by the deep seismic reflection profiles further supports the superficial tectonic model. The near NEE orientation of the stress field in North China and the lower strike-slip movement component of the Tanlu fault zone make it easy to faulting in the Tangshan-Hejian-Xingtai fault zone, which lies diagonally in the middle rectangular area of the North China plain faulted basin. The detailed structural model of the seismogenic fault obtained by various detection methods is of great scientific significance for understanding the seismogenic mechanism of the Tangshan earthquake.